Developing understanding of information literacy within the Croatian school environment - Špiranec, Sonja (Array, 2011)
This chapter presents efforts made to promote information literacy among school library practitioners and the wider school community in Croatia. The authors present results of the pilot project carried out with the Education and Teacher Training Agency in advocating and developing understanding of information literacy within the Croatian school environment. The workshop linked educational sessions with the observations and suggestions of participants in order to form a platform for creating a national information literacy agenda for school communities. The aim of the project “Information Literacy in School Libraries” was to show how a bottom-up approach developed through a collaborative process that included different representatives from the school community could be used in formulating sustainable and real-life strategies for promotion and advancement of information literacy in Croatia.